Blind Spot in the Radar of MEST-C Score: Type and Severity of Tubulointerstitial Nephritis in IgA Nephropathy - Iram Asrar; Mudassar Hussain; Aurangzeb Afzal; Usman Hassan; Sheeba Ishtiaq (International Journal of Nephrology)
Background. The updated version of predictive classification for immunoglobulin A nephropathy (IgAN) prognosis “The Oxford Classification” identifies five histopathological features including mesangial hypercellularity (M), endocapillary proliferation (E), segmental glomerulosclerosis (S), tubular atrophy/interstitial fibrosis (T) and crescents (C), the MEST-C. However, few studies suggest that tubulointerstitial inflammation, which is not included in the MEST-C, is also linked to disease progression and is, consequently, a neglected determinant of prognosis among others. Therefore, there is a need to evaluate this histopathological parameter in patients with IgA nephropathy. Materials and Methods. This cross-sectional descriptive study was conducted at Shaukat Khanum Memorial Cancer Hospital and Research Center, Lahore, Pakistan. Data of histopathological and immunofluorescence proven renal biopsies (300) of IgA nephropathy patients from January 2016 through May 2022 were extracted using a convenient sampling technique. Biopsies were histologically reviewed for type and severity of tubulointerstitial inflammation, in addition to the MEST-C score. Renal biopsies of patients who had a history of transplant, autolyzed tissue, no glomeruli on histological examination, and/or a tubular atrophy/interstitial fibrosis score of 2 (T2) in MEST-C scoring were excluded. Data were analyzed using SPSS 20. An association between the variables was analyzed using the chi-square and Fischer exact tests. A p value less than 0.05 was considered statistically significant. Results. A total of 247/300 biopsies were eligible for inclusion. The mean age at the time of biopsy was 31.90 ± 12.48 with 63.6% in the age group between 21 and 40 years, and 69.6% were male. Tubulointerstitial inflammation was observed in 90.2% cases with 49.4% showing moderate while 4.5% showing severe degree of inflammation. A strong association of both the type and severity of tubulointerstitial inflammation was found with M, E, T, and C scores (p value < 0.05). Conclusion. The high-frequency and strong statistical association of tubulointerstitial inflammation with the M, E, T, and C scores in our study elucidate its prognostic role in the progression and management of IgA nephropathy.